2004
DOI: 10.1136/bmj.38043.501690.7c
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double blind, placebo controlled comparison of ginkgo biloba and acetazolamide for prevention of acute mountain sickness among Himalayan trekkers: the prevention of high altitude illness trial (PHAIT)

Abstract: Objective To evaluate the efficacy of ginkgo biloba, acetazolamide, and their combination as prophylaxis against acute mountain sickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 9 publications
1
99
1
1
Order By: Relevance
“…In addition, after 24 h, 78% of the obese males had AMS scores of o4 while only 40% of the nonobese males had scores at or above this level. This 78% incidence of AMS in the obese population far exceeds that for healthy individuals travelling to high altitudes [40,199,200].…”
Section: Obesity Hypoventilationmentioning
confidence: 99%
“…In addition, after 24 h, 78% of the obese males had AMS scores of o4 while only 40% of the nonobese males had scores at or above this level. This 78% incidence of AMS in the obese population far exceeds that for healthy individuals travelling to high altitudes [40,199,200].…”
Section: Obesity Hypoventilationmentioning
confidence: 99%
“…However, the PHAIT trial (prevention of high altitude illness trial) showed that it does not seem to be efficacious for preventing AMS compared to results from acetazolamide. 56 Aspirin, at a dose of 325 mg three times daily, seems to reduce the incidence of headache associated with physical exertion at high altitude. 57 Different recommendations on preventive measures for HAH, are listed in Table 5 according to level of evidence.…”
Section: Acute Mountain Sicknessmentioning
confidence: 99%
“…The dose can be divided and climbers can take 125 mg twice a day [20]. The clinical trials demonstrate that the dose of 500 mg/day is effective to prevent AMS [20,21]. By inhibiting carbonate anhidrosis in kidneys, acetazolamide induces metabolic acidification, which results in quicker reactions of chemoreceptors to hypoxia associated with high altitudes.…”
Section: Pharmacological Prophylacticsmentioning
confidence: 99%